Novel Synthesis of Polyimide Foams with Aromatic and 1,6-Diaminohexane Imide Bonding - Dong-Sen Chen; Chun-Hua Chen; Wha-Tzong Whang; Chun-Wei Su (Advances in Polymer Technology)
A novel type of polyimide foams (PIFs) with chemically inserted flexible aliphatic diamine (1,6-diaminohexane (HMDA)) segments was successfully synthesized and characterized in this research. The aliphatic HMDA segments were randomly incorporated in the long chain aromatic imide bonds. The obtained PIFs containing various HMDA contents (0 to 20 mol%) exhibited different morphologies such as lowered density and larger cell diameter (with higher HMDA content), and open cell ratio was increased as well. HMDA rendered flexibility to the copolymer leading to decreased rigidity. Compared to using 4,4′-oxydianiline (ODA) as the sole diamine source, incorporating low cost of HMDA would increase the PIF’s flexibility and improve its processibility while making the production more cost effective. Within some range of compromised thermal and mechanical properties, this proposed method could be feasible for industrial applications.